2012
DOI: 10.1051/0004-6361/201117592
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking atomic data for the CHIANTI atomic database: coronal lines observed by Hinode EIS

Abstract: The coronal lines that are observable in the Hinode EUV Imaging Spectrometer (EIS) wavelengths are assessed with new atomic data that have recently become available for a range of important ions. EIS spectral lines are identified based on their spatial variation across different solar regions, their wavelengths, and their intensities. Two off-limb observations are presented, one above an active region, and one in the quiet Sun. The spectra are relatively free of low-temperature lines. Accurate wavelengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 44 publications
6
55
1
Order By: Relevance
“…Del Zanna et al (2004) presented new identifications and a set of new observed energies that are adopted here. The energies of the 3s 2 3p 4 3d levels have all been confirmed with recent, accurate EUV observations with the Hinode EUV Imaging Spectrometer (Del Zanna 2012).…”
Section: Previous Observations and Atomic Data For Fe Xsupporting
confidence: 76%
“…Del Zanna et al (2004) presented new identifications and a set of new observed energies that are adopted here. The energies of the 3s 2 3p 4 3d levels have all been confirmed with recent, accurate EUV observations with the Hinode EUV Imaging Spectrometer (Del Zanna 2012).…”
Section: Previous Observations and Atomic Data For Fe Xsupporting
confidence: 76%
“…The corresponding response for this band was calculated by adding the Fe xiv emissivity to the continuum. The atomic data for Fe xiv are reliable (Liang et al 2010;Del Zanna 2012b) and the 211.3 Å line does not have significant temperature or density effects.…”
Section: Aia 131 åmentioning
confidence: 79%
“…The Hinode EUV Imaging Spectrometer (EIS), with its two channels (SW: 166-212 Å; LW: 245-291 Å), has provided (since 2006) AR observations in a wide range of temperatures (e.g. from all the iron ionisation stages from Fe vii to Fe xvi and above 10 MK from Fe xxiii and Fe xxiv, as presented in detail in Del Zanna 2009a;Del Zanna 2012b, 2008Del Zanna et al 2011b). We have also recently provided an in-flight calibration for EIS (Del Zanna 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Young et al 2009) that these diagnostics produce higher densities than those obtained with other ions formed close in temperature. A full benchmark of the coronal density diagnostics available to Hinode EIS was performed by Del Zanna (2012), where these inconsistencies, although not very large, were confirmed. We therefore aim to investigate whether a larger calculation can resolve these discrepancies.…”
Section: Introductionmentioning
confidence: 95%